Gender Equality and Health in High-Income Countries: A Systematic Review of Within-Country Indicators of Gender Equality in Relation to Health Outcomes - Allison Milner; Anne Kavanagh; Anna J. Scovelle; Adrienne O'Neil; Guyonne Kalb; Belinda Hewitt; Tania L. King (Mary Ann Liebert, 2021)
Background: Gender equality is recognized as an important political, social, and economic goal in many countries around the world. At a country level, there is evidence that gender equality may have an important influence on health. Historically gender equality has mainly been measured to allow for between-country, rather than within-country comparisons; and the association between gender equality and health outcomes within countries has been under-researched. This article thus aimed to systematically review within-country indicators of gender equality in public health studies and assess the extent to which these are related to health outcomes. Materials and Methods: We used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach with two independent reviewers. Results: Data from the eight included studies revealed that there was heterogeneity in the way gender equality has been measured as a multidimensional construct. Associations between gender equality and a number of different health outcomes were apparent, including mortality, mental health, morbidity, alcohol consumption, and intimate partner violence, with gender equality mostly associated with better health outcomes. Conclusions: Further investigation into the effects of gender equality on health outcomes, including a clear conceptualization of terms, is critical for the development of policies and programs regarding gender equality.